Al-Qur’an Dan Urgensinya Dalam Kehidupan Manusia - Atika Septina; Muyasaroh Muyasaroh; Dwi noviani; Destri Wulandari (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
The Qur’an serves as a guide for mankind, so every meaning must be understood with full heart. This writing uses library research, which means gathering data or work of scientific writing and analyzing data on the problem being studied. This is to explain the Qur’an and its importance to humans. The Qur’an, which is the revelation and the word of Allah revealed to mankind through the Prophet Muhammad, is the unquestionable book and is rich in everything. This book is also the most important source of Islam, and is the guideline of life for every person who has Islamic religion, as well as for all mankind. The Qur’an not only provides guidance on human relations with God, but also regulates human relationships with one another and the way they interact with each other.